Validation of lean manufacturing implementation framework using Delphi technique - Nordin, Norani; Md Deros, Baba; Abdul Wahab, Dzuraidah; Ab. Rahman, Mohd Nizam (Penerbit UTM Press, 2012)
Lean manufacturing is a proven approach for success in manufacturing industry.However, several organisations failed in their attempt to implement lean manufacturing system The transition to lean manufacturing requires radical change which involves a total reshaping of purpose, system and culture of the organisation Therefore, a lean manufacturing implementation framework was developed This framework is Intended to provide practitioners with a better understanding of lean transition and minimize the conflicts of implementing lean manufacturing system The purpose of this paper is to validate the proposed lean manufacturing implementation framework using Delphi technique.This technique is a process of gathering opinions of experts, which designed to achieve a convergence of opinions on a specific real-world Issue The work continued over two iterative rounds until consensus or stability is reached Comments and suggestions given by the experts help to further Improve and validate the framework As conclusion,the final framework of lean manufacturing implementation is presented.